A Pathogen-Inducible Rice NAC Transcription Factor ONAC096 Contributes to Immunity Against Magnaprothe oryzae and Xanthomonas oryzae pv. oryzae by Direct Binding to the Promoters of OsRap2.6, OsWRKY62, and OsPAL1 - Wang, Hui; Bi, Yan; Gao, Yizhou; Yan, Yuqing; Yuan, Xi; Xiong, Xiaohui; Wang, Jiajing; Liang, Jiayu; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2021)
The rice NAC transcriptional factor family harbors 151 members, and some of them play important roles in rice immunity. Here, we report the function and molecular mechanism of a pathogen-inducible NAC transcription factor, ONAC096, in rice immunity against Magnaprothe oryzae and Xanthomonas oryzae pv. oryzae. Expression of ONAC096 was induced by M. oryzae and by abscisic acid and methyl jasmonate. ONAC096 had the DNA binding ability to NAC recognition sequence and was found to be a nucleus-localized transcriptional activator whose activity depended on its C-terminal. CRISPR/Cas9-mediated knockout of ONAC096 attenuated rice immunity against M. oryzae and X. oryzae pv. oryzae as well as suppressed chitin- and flg22-induced reactive oxygen species burst and expression of PTI marker genes OsWRKY45 and OsPAL4; by contrast, overexpression of ONAC096 enhanced rice immunity against these two pathogens and strengthened chitin- or flg22-induced PTI. RNA-seq transcriptomic profiling and qRT-PCR analysis identified a small set of defense and signaling genes that are putatively regulated by ONAC096, and further biochemical analysis validated that ONAC096 could directly bind to the promoters of OsRap2.6, OsWRKY62, and OsPAL1, three known defense and signaling genes that regulate rice immunity. ONAC096 interacts with ONAC066, which is a positive regulator of rice immunity. These results demonstrate that ONAC096 positively contributes to rice immunity against M. oryzae and X. oryzae pv. oryzae through direct binding to the promoters of downstream target genes including OsRap2.6, OsWRKY62, and OsPAL1.